2005
DOI: 10.3168/jds.s0022-0302(05)72682-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Corn Silage Hybrid with High Cell-Wall Content and Digestibility with a Hybrid of Lower Cell-Wall Content on Performance of Holstein Cows

Abstract: We hypothesized that substituting a corn hybrid with high cell-wall content and high neutral detergent fiber (NDF) digestibility (HCW) for a hybrid with lower cellwall content and lower NDF digestibility (LCW) would improve feed intake and milk production in lactating Holstein cows. There was a 3.6 percentage unit difference in NDF content and a 4.1 percentage unit difference in 30-h in vitro NDF digestion between the 2 corn hybrids. In trial 1, 40 cows (12 primiparous) ranging in milk production from 24.1 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
14
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 22 publications
5
14
1
3
Order By: Relevance
“…Ivan et al (2005) showed that feeding silage from maize hybrids with a high cell wall content and high aNDFD resulted in higher DMI and milk yield compared to feeding a hybrid with a lower cell wall content and low aNDFD. Similarly, Boon et al (2012) analyzed changes during the growing season in the anatomy, chemical composition, and fermentation characteristics of maize stem from a lower internode (internode 7) of two forage maize cultivars differing in whole plant digestibility.…”
Section: Resultsmentioning
confidence: 99%
“…Ivan et al (2005) showed that feeding silage from maize hybrids with a high cell wall content and high aNDFD resulted in higher DMI and milk yield compared to feeding a hybrid with a lower cell wall content and low aNDFD. Similarly, Boon et al (2012) analyzed changes during the growing season in the anatomy, chemical composition, and fermentation characteristics of maize stem from a lower internode (internode 7) of two forage maize cultivars differing in whole plant digestibility.…”
Section: Resultsmentioning
confidence: 99%
“…The positive effects of enhanced IVFD on productivity of lactating dairy cows have been reported for corn silage (Thomas et al 2001;Neylon and Kung, Jr. 2003;Ivan et al 2005), sorghum silage (Grant et al 1995;Aydin et al 1999;Oliver et al 2004), and alfalfa silage (Dado and Allen 1996). Whole-plant barley silage (WPBS) is the primary forage used by dairy producers in western Canada, but little is known about factors affecting IVFD and its effects on animal performance.…”
mentioning
confidence: 99%
“…Moreover, it is increasingly important to develop corn hybrids of higher rumen DM digestibility (Ivan et al, 2005). A NDF of higher digestibility is recommended, aiming at increased DM intake, and consequent increase in nutrient intake (Mertens, 1987).…”
Section: Discussionmentioning
confidence: 99%